An origami paper-based bacteria-powered battery. (July 2015) - Lee, Hankeun; Choi, Seokheun
Abstract: A fully-integrated self-powered system on paper will work independently and self-sustainably as a low-cost and disposable diagnostic device in challenging field conditions such as resource-limited and remote regions. The paper-based power source is essential to create the paper-based system. In this work, a stackable and integrative 3-D paper-based bacteria-powered battery was developed. The battery was capable of generating power from microbial metabolism, delivering on-board energy to the next generation of paper-based systems with one drop of bacteria-containing liquid derived from renewable and sustainable water and wastewater sources (e.g. wastewater, municipal wastes, biomass and watershed) that are readily accessible in the local environment. An inexpensive air-breathing cathode was also created on paper with activated carbon on the sprayed Nickel electrode. By applying origami techniques, compact and stackable 3-D battery structures were created from 2-D sheets through high degrees of folding along pre-defined creases. The bacterial culture was added into two common inlets of the folded battery stack, through which it was transported into each battery. For operation, the battery stack was unfolded to expose all air-cathodes to the air, thereby maximizing their cathodic reactions. Graphical abstract: highlights: A stackable and integrative 3-D paper-based bacteria-powered battery was developed. The battery generated power from microbial respiration. An air-cathode was created on paper with activated carbon.